Multiple Avenues of Intermediation, Corporate Finance and Financial Stability - Davis, E. (IMF Working Papers; Working Paper ;, 2001)
Using data from the US, UK, Japan and Canada, this paper provides evidence on the benefits to an economy from "multiple avenues of intermediation". The overall conclusion is that the existence of active securities markets alongside banks is indeed beneficial to the stability of corporate financing, both during cyclical downturns and during banking and securities market crises. The benefit from multiple avenues are greater, the more comparable the size of securities market and intermediated financing, as well as the larger the proportion of companies able to access both loan and securities markets. The analysis raises a number of policy issues and research topics for further investigation.